Interprofessional education in aged-care facilities: Tensions and opportunities among undergraduate health student cohorts. Issue 5 (2nd September 2016) - Annear, Michael; Walker, Kim; Lucas, Peter; Lo, Amanda; Robinson, Andrew
ABSTRACT: This article examines the reflective discourses of medical, nursing, and paramedic students participating in interprofessional education (IPE) activities in the context of aged-care clinical placements. The intent of the research is to explore how students engage with their interprofessional colleagues in an IPE assessment and care planning activity and elucidate how students configure their role as learners within the context of a non-traditional aged-care training environment. Research participants included cohorts of volunteer medical ( n = 61), nursing ( n = 46), and paramedic ( n = 20) students who were on clinical placements at two large teaching aged-care facilities in Tasmania, Australia, over a period of 18 months. A total of 39 facilitated focus group discussions were undertaken with cohorts of undergraduate student volunteers from three health professions between February 2013 and October 2014. Thematic analysis of focus group transcripts was assisted by NVIVO software and verified through secondary coding and member checking procedures. With an acceptable level of agreement across two independent coders, four themes were identified from student focus group transcripts that described the IPE relations and perceptions of the aged-care environment. Emergent themes included reinforcement of professional hierarchies, IPE in aged care perceived as mundane and extraneous, opportunities for reciprocal teaching and learning, and understanding interprofessional roles. While not all students can be engaged with IPE activities in aged care, our evidence suggests that within 1 week of clinical placements there is a possibility to develop reciprocal professional relations, affirm a positive identity within a collaborative healthcare team, and support the health of vulnerable older adults with complex care needs. These important clinical learnings support aged-care-based IPE as a potentially powerful context for undergraduate learning in the 21st Century.